1989
DOI: 10.1002/jsfa.2740490206
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of starch by incubation with rumen fluid. A comparison of different starch sources

Abstract: The degradability of starch fiom various feedstuffs was investigated in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 13 publications
3
22
0
2
Order By: Relevance
“…Starch digestion in the rumen varies markedly among feeds (Cone et al, 1989). Maize starch is less degradable in the rumen than barley or wheat starch (Theurer, 1986), which has consequences not only for starch digestion but also for fibre digestion in the rumen, which tends to decrease with the addition of rapidly degradable starch (DePeters and Taylor, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Starch digestion in the rumen varies markedly among feeds (Cone et al, 1989). Maize starch is less degradable in the rumen than barley or wheat starch (Theurer, 1986), which has consequences not only for starch digestion but also for fibre digestion in the rumen, which tends to decrease with the addition of rapidly degradable starch (DePeters and Taylor, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Malestein et al (1988) showed clear differences in starch degradation upon incubation with rumen fluid or cr-amylase. Cone et al (1989) showed a constant order in degree of digestibility of different starches upon incubation with rumen fluid from cows fed on three different rations. It was not possible to accurately predict the rate of starch degradation by rumen fluid with enzymic degradation (Cone and Vlot 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro estimates of starch degradation rate relating to the small intestine have proved to be unreliable during a previous modelling attempt (Ewing and Johnson, 1987). Data is available relating to incubations with the appropriate enzymes such as those found in pancreatin (Cone et al, 1989;Cone, 1991) or intestinal mucosa extractions (Coombe and Siddons, 1973). However, problems arise when these values are applied to starch degradation as it occurs in the small intestine.…”
Section: In Vitro Determination Of Small Intestinal Starch Degradationmentioning
confidence: 99%